The Venture Bros. Season 7 [videorecording (DVD)] (Warner Home Video., 2019)
"Jonny Quest" gets an irreverent but affectionate spoofing in this animated series chronicling the sometimes hair-raising adventures of Hank and Dean Venture, the not-especially-bright twin sons of pill-popping "super-scientist" Dr. Thaddeus "Rusty" Venture. Luckily (for the most part), their safety is overseen by a security guard who uses his license to kill every chance he gets